2008
DOI: 10.1177/010740830802800303
|View full text |Cite
|
Sign up to set email alerts
|

Nurses Conceptions of the Professional Role of Operation Theatre and Psychiatric Nurses

Abstract: The shortage of specialist trained nurses in the operating theatre and psychiatric care is a problem in Swedish health care. There is a great need for recruitment since in both areas nurses have a high average age and few students register in these specialties at university. The reason for the low interest for these specialties is not clear. The purpose of the study was to investigate nurses' and nurse students' conceptions of the professional role of operating theatre and psychiatric care nurses. A qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Within professional psychology for example, it was suggested that the focus counselling psychology places on individuals' strengths and assets (Goodyear et al, 2016) helps the specialty maintain its integrity and identity (Lopez et al, 2006). In contrast, it is argued that there is a lack of clarity regarding the nursing role (Blegeberg et al, 2008) and community mental health nurses (CMHNs) struggle to articulate their profession in a way that clearly distinguishes them from other professions (Crawford et al, 2008). Professions must work for the benefit of others, promoting public good (Bhugra, 2008a;Bhugra, 2009;Bhugra & Gupta, 2010;Ikkos & Mace, 2009;Randall & Kindiak, 2008;Roberts, 2009;Robertson & Walter, 2007).…”
Section: # $mentioning
confidence: 99%
See 1 more Smart Citation
“…Within professional psychology for example, it was suggested that the focus counselling psychology places on individuals' strengths and assets (Goodyear et al, 2016) helps the specialty maintain its integrity and identity (Lopez et al, 2006). In contrast, it is argued that there is a lack of clarity regarding the nursing role (Blegeberg et al, 2008) and community mental health nurses (CMHNs) struggle to articulate their profession in a way that clearly distinguishes them from other professions (Crawford et al, 2008). Professions must work for the benefit of others, promoting public good (Bhugra, 2008a;Bhugra, 2009;Bhugra & Gupta, 2010;Ikkos & Mace, 2009;Randall & Kindiak, 2008;Roberts, 2009;Robertson & Walter, 2007).…”
Section: # $mentioning
confidence: 99%
“…CMHNs have described their role as being and helping to and (Crawford et al, 2008). Consequently, an and ability is highly regarded whilst working in mental health services (Blegeberg et al, 2008).…”
Section: $ #mentioning
confidence: 99%
“…Studies show that nursing students are prejudiced and anxious when encountering people with mental illnesses (Blegeberg et al, 2008;Curtis, 2007;Hercelinskyj, Cruickshank, Brown, & Phillips, 2014). Students' predisposed impressions are linked to societal attitudes and stigma of mental illness (Charleston & Happell, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Theatre nurses regard their profession as a challenge and choose it out of fascination, even if other nurses feel that this specialisation does not include ‘real nursing care’ (15). Theatre nurses have been called technicians, robots or trained monkeys who do not care about the patients (16) and are dependent assistants, responsible monitors and fragmented nurses with no relationship with the patient (17). However, theatre nurses are fully aware that their first priority in their work in the operating theatre is nursing care to guarantee the patient’s well‐being (16).…”
Section: Introductionmentioning
confidence: 99%